Unveiling Online Violence Against Women in Politics: EU Political Candidates - Espírito-Santo, Ana; Santos; Batista, F. (IPSA 75th Anniversary Conference, 2024)
This paper focuses on the phenomenon of violence against women in politics in the online space, specifically on the X platform (formerly known as Twitter). This platform is commonly used by politicians but serves as a prominent stage for impulsive and malicious discourse. We analyze online discourse on X in the form of tweets, produced by common citizens and directed at female and male candidates for Prime Minister or Head of State, in order to answer the following research questions: What characterizes the online violence that both female and male candidates experience? How frequently do female candidates experience online violence against women? What factors (individual and political) might be associated with a higher or lower level of online violence against women in politics? The paper draws on an original dataset of tweets. All legislative and presidential elections held within the last three years in European Union (EU) countries that had at least one woman among the four most voted candidates for Prime Minister or Head of State were selected. In total, we were left with 49 candidates (17 women and 32 men) from twelve EU countries comprising more than 30000 tweets.